What is Changing in Indications and Treatment of Focal Nodular Hyperplasia of the Liver. Is There Any Place for Surgery? - Perrakis, Aristotelis; Vassos, Nikolaos; Grützmann, Robert; Croner, Roland S. (Annals of Hepatology, 2017)
Focal nodular hyperplasia (FNH) is a common benign liver tumor, which occurs in the vast majority of the cases in young women. FNH represents a polyclonal lesion characterized by local vascular abnormalities and is a truly benign lesion without any potential for malignant transformation. A retrospective single institution analysis of 227 FNH patients, treated from 1990 to 2016 and a review of studies reporting surgical therapy of overall 293 patients with FNH was performed. Indications for resection with a focus on diagnostic workup, patient selection, surgical mode and operative mortality and morbidity have been analysed. Ninety three patients underwent elective hepatectomy and 134 patients observation alone, where median follow-up was 107 months. Postoperative complications were recorded in 14 patients, 92% of patients reported an improvement with respect to their symptoms. Overall among 293 patients underwent surgery in the series, included to this review, there was a morbidity of 13%, where median follow-up was 53 months. Systematic follow-up remains the gold standard in asymptomatic patients with FNH. However elective surgery should be considered in symptomatic patients, in those with marked enlargement and in case of uncertainty of diagnosis. Surgery for FNH is a safe procedure with low morbidity and very good long term results as far as quality of life after surgery is concerned and surely an integral part of the modern management of FNH.
EVALuna2:15281